"Expropriation of Capitalist by State Capitalist:" Organizational Change and the Centralization of Capital as State Property. (8th August 2022) - Alami, Ilias; Dixon, Adam D.
Abstract: State enterprises, sovereign funds, and other state–capital hybrids have become major engines of global capitalism. How can we explain their global rise and organizational transformation into increasingly sophisticated and globally competitive forms? Why do they increasingly emulate the practices and organizational goals of comparable private-sector entities, adopt the techniques of modern finance, resort to mixed ownership, and extend their operations across geographic space? After critically engaging with arguments that emphasize the role of firm strategies, developmentalist logics, financialized norms, and Polanyian double movements, we develop an explanatory model of organizational change grounded in historic–geographic materialism and economic geographies of the firm. We locate the expansion of state ownership (the role of states as owners) in the historic development and geographic remaking of global capitalism and, in particular, the emergence of a new constellation of international divisions of labor. This created the conditions for a massive round of centralization of capital as state property (the mass of capital controlled by states) since the early 2000s. The modern, marketized, globally spread state–capital hybrid emerged as an organizational fix to mediate the geographic contradictions and imperatives associated with this process. Purposive organizational adaption consisted in developing new skills, operational capabilities, and mixed-ownership structures in order to leverage the financial system, allow for the development of liquid forms of state property, and facilitate the expansion of the latter into global circuits of capital. As such, the article contributes to debates on the role of the state in global value chains, the firm-state nexus, and state capitalism.